STUDY ON MICROALBUMINURIA IN APPARENTLY NORMAL POSTMENOPAUSAL WOMEN - GN, Deepti; K, Lakshmi; S, Sumathi (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Introduction: Microalbuminuria is usually estimated in diabetic and in patients with risk of renal problems. Objective: Our aim is to study the occurrence of microalbuminuria in apparently normal postmenopausal women and also to find out the relationship between microalbuminuria and cardiovascular risk factors. Methods: the study was conducted in a tertiary care hospital, Puducherry for a period of 4 months. Serum and urine samples were taken from forty four apparently normal postmenopausal women. Urea, Creatinine, Uric acid levels and lipid profile from serum samples and microalbumin, creatinine levels from urine samples were estimated. Urine albumin creatinine ratio and Glomerular Filtration Rate were calculated using standard methods. Results: 48percent of the women in our study had microalbuminuria. Microalbuminuria positive subjects had higher TC, LDL, TGL and VLDL levels when compared to microalbuminuria negative subjects. Conclusion: Occurrence of microalbumuria in normal postmenopausal women and significantly higher risk of abnormal lipid profile in them favours the importance of screening of microalbuminuria in apparently normal postmenopausal women also. Keywords : Microalbuminuria, Postmenopausal women, lipid profile, renal parameters.